Severe haematological involvement in children with systemic lupus erythematosus and clinical associations - Kisaoglu, Hakan; Sener, Seher; Demirbas, Kaan Can; Demir Yigit, Yasemin; Garipcin, Pinar; Coskun, Serkan; Kalyoncu, Mukaddes (Oxford Univ Press, 2025)
Objectives: To investigate the severe haematological involvement in children with SLE and assess its clinical associations, treatments, outcome and damage accrual. Methods: The medical charts of children with SLE in whom haematological involvement was observed were reviewed. Severe haematological indices were defined as autoimmune haemolytic anaemia with a haemoglobin concentration <8 g/dl, thrombocyte count <30 000/mu L and neutrophil count <500/L. Results: Among the 224 patients included, 102 (45.5%) displayed severe indices, predominantly at the initial involvement, and most frequently as severe anaemia in 54 (24.1%) and severe thrombocytopenia in 45 (20.1%). Disease activity did not differ according to the presence of severe disease indices. In addition, the presence of severe indices at initial involvement did not affect the damage accrual. However, a higher rate of damage (51.1% vs 29.9%, P = 0.002) and steroid-induced damage (28.9% vs 8.2%, P < 0.001) was evident in patients with flares of the haematological system. Regression analysis revealed that rituximab treatment during the initial episode (OR: 4.5, P = 0.006) and the presence of anticardiolipin antibodies (OR: 2.3, P = 0.014) significantly increases the odds for haematological system flare. However, severe indices at initial involvement did not increase the odds of a haematological flare. Conclusion: Severe haematological indices at onset are common but not related with disease outcomes. Prevention of flares is important to improve outcomes, and a more rigorous maintenance strategy would benefit most to children who display haematological indices refractory to conventional immunosuppressants and those with anti-cardiolipin antibodies.
Keywords: children; damage; flare; haematological involvement; systemic lupus erythematosus; treatment